Educational Reconstruction: A Study of Paulo Freire's Thought - Nur, Muh. Yasin Ceh (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The purpose of this research is to find out and understand to teaching staff that today's education is not relevant to educational goals, so Paulo Freire wants to reconstruct this education. This research is qualitative, using library research data collection methods. Data source: Because this article is a study of the work of a figure, the data used is more library data, so the author collects literature, including books and articles related to the figure to be discussed. In analyzing data, researchers try to find meaning by trying to reveal the implied and explicit meanings. The result of this article is the reconstruction of education carried out by Paulo Freire because education is currently shifting towards the bank system. Today's teaching system is known as a passive learning model, namely, the teacher explains, the students listen, the teacher dictates, the students take notes, the teacher asks, the students answer, and so on. Therefore, Paulo Freire wanted education must provide liberation, learning must be carried out using methods of dialogue, facing problems, raising awareness, and liberating education.